Pencarian dan Pemanfaatan Informasi Data Badan Meteorologi, Klimatologi, dan Geofisika (BMKG) - Benny Hartanto; Ningrum Astriawati; Damar Kuncoro Yekti; Supartini Supartini (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The Meteorology, Climatology, and Geophysics Agency (BMKG) has the task of carrying out government duties in the fields of Meteorology, Climatology, Air Quality, and Geophysics by the provisions of the applicable legislation.  This study aims to search and utilize BMKG meteorological data in the Yogyakarta area. This research was conducted at the Mlati Climatology Station, Sleman, Yogyakarta. The analysis used uses descriptive analysis. The data collection method uses observation techniques, interviews, documentation from offline data centers, and BMKG online data. From the results of the study, the search for meteorological data of BMKG Yogyakarta for the benefit of the community includes inputting data until processing until it is published to the public through social media such as Whatsapp, Instagram, Facebook, Twitter, Email, Radio, and Television. The utilization and importance of BMKG weather information are very influential for the survival of the people in Yogyakarta. With the information from the BMKG, the community can know the weather forecasts in the next few days and adjust the work that makes the weather as its indicator such as farming, tourism, fisheries, transportation, trade, and government as well as government agencies working in the field of disaster management.